2016
DOI: 10.1108/sajgbr-01-2015-0007
|View full text |Cite
|
Sign up to set email alerts
|

CSR in Afghanistan: a global CSR agenda in areas of limited statehood

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 69 publications
(106 reference statements)
0
29
0
Order By: Relevance
“…After decades of political volatility, conflicts with the opposition and insecurity, Afghanistan's economy has recently experienced unparalleled growth in GDP of 10-22% annually. Economic growth has been attributed to low GDP baselines, the denationalization of the economy, and importantly, the massive influx of international assistance (Azizi and Jamali, 2016).…”
Section: Iranian and Afghan Contextsmentioning
confidence: 99%
“…After decades of political volatility, conflicts with the opposition and insecurity, Afghanistan's economy has recently experienced unparalleled growth in GDP of 10-22% annually. Economic growth has been attributed to low GDP baselines, the denationalization of the economy, and importantly, the massive influx of international assistance (Azizi and Jamali, 2016).…”
Section: Iranian and Afghan Contextsmentioning
confidence: 99%
“…It is well said that every Afghan employee knows at least someone who was kidnapped for ransom [6], but despite such dangers, employees cannot stay home. Working outside home as employees in such a war-stricken zone exposes them to extreme external stresses, threats, hazards, and shocks e.g., being fired on or being near gunfire in the street; hearing bombs and gunfire in the distance; seeing people killed; experiencing arrest and torture; and being exposed to death and mutilation [7][8][9]. A recent report by the "Save the Children" organization showed that 550 children were dead as the result of war and conflict between these political parties in Afghanistan.…”
Section: Introductionmentioning
confidence: 99%
“…This underscores the challenges of applying what might be global models of CSR to local contexts in developing countries, 76 or to areas of limited state presence or 'statehood'. 77 Emerging approaches to CSR tailored to fragile or developing contexts may be more helpful. Visser suggests CSR strategies should make clear economic contributions and account for 'dilemmas or trade-offs' such as economic development versus environmental protection.…”
Section: Discussionmentioning
confidence: 99%